Network models in finance expanding the tools for portfolio and risk management - Fabozzi, Frank J.; Konstantinov, Gueorgui S. (John Wiley & Sons Inc., 2025)
"*Network Models in Finance: Expanding the Tools for Portfolio and Risk Management* explores the application of network theory to asset management, emphasizing how network-based methodologies can enhance portfolio and risk management. The book integrates quantitative modeling, causal relationships, and optimization within a network framework, extending beyond traditional asset management tools. It provides a comprehensive overview of graph-theoretical approaches and practical implementations using R, bridging classical methods with modern financial data science. By offering both theoretical insights and practical applications, the book aims to address complex challenges in finance, making it a valuable resource for practitioners and academics seeking advanced network-based solutions in asset management"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Portfolio management -- Mathematical models; Financial risk management -- Mathematical models; System analysis; Gestion de portefeuille; Modèles mathématiques; Finances; Gestion du risque; Modèles mathématiques; Analyse de systèmes; systems analysis